Structural Behavior of Novel Hybrid Composite Beams Made of Geopolymer Concrete and High-Performance Concrete (HPC) - Wong , Joel Weng Lok (Universiti Teknologi PETRONAS, 2020)
The cement industry has been making a significant production of carbon dioxide gas emissions that will cause pollution to the atmosphere. The carbon dioxide gas production is based from the process of burning huge quantities of fuel and inherent to the basic calcinations process of limestone. During Portland cement manufacturing process, a huge among of carbon dioxide emissions and other greenhouse gases will be produced. Traditional way of by increase the depth and diameter of reinforcement bar had come to a critical point that this method no longer improved the structural behavior of beam but bringing ill effect to the overall project. Moreover, Ordinary Portland Cement (OPC) are usually unable to resist when expose to fire, high temperature, sulphate, acid and tension. All this situation will reduce the durability of concrete.